Magnetic field-enhanced cellular uptake of doxorubicin loaded magnetic nanoparticles for tumor treatment. (2nd September 2016) - Venugopal, Indu; Pernal, Sebastian; Duproz, Alexandra; Bentley, Jeromy; Engelhard, Herbert; Linninger, Andreas
Abstract: Cancer remains the second most common cause of death in the US, accounting for nearly 1 out of every 4 deaths. In recent years, several varieties of nanoparticles (NPs) have been synthesized with the intent of being utilized as tumor drug delivery vehicles. We have produced superparamagnetic, gold-coated magnetite (Fe3 O4 @Au) NPs and loaded them with the chemotherapeutic drug doxorubicin (DOX) for magnetic drug targeting (MDT) of tumors. The synthetic strategy uses the food thickening agent gellan gum (Phytagel) as a negatively charged shell around the Fe3 O4 @Au NP onto which the positively charged DOX molecules are loaded via electrostatic attraction. The resulting DOX-loaded magnetic nanoparticles (DOX-MNPs) were characterized using transmission electron microscopy, energy dispersive x-ray spectroscopy, superconducting quantum interference device magnetometry, surface area electron diffraction, zeta potential measurements, fourier transform infrared spectroscopy as well as UV/Vis and fluorescence spectroscopy. Cytotoxicity of the DOX-MNPs was demonstrated using the MTT [3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide] assay on C6 glioma cells. Cellular uptake of DOX-MNPs was enhanced with magnetic fields, which was quantitatively determined using flow cytometry. This improved uptake also led to greater tumor cell death, which was measured using MTT assay. These MDT results are promising for a new therapy for cancer.